Control de velocidad en lazo cerrado de un motor trifásico de inducción jaula de ardilla con centro de operación y monitoreo remoto desde un PC. - Conza Zhingre, Férdinan Francisco (2011)
This paper aims to contribute to the teaching-learning process of students in the career of Electromechanical Engineering, National University of Loja. The student will benefit by implementing this system will be the acquisition of knowledge, skills and abilities, since they can perform various experimental tests that will help improve vocational training in the practical scope of a university student. We present a system that controls, measures, displays, processes and stores data for the variables that characterize the system performance of a remote control three-phase AC motor, for that SCADA was developed using the programming tool of National Instrument LabVIEW version 8.2 running on Windows operating system, to command a cFP-2020 PLC via Ethernet, which is connected to the analog inputs to a SINAMICS G110 frequency inverter. The data captured in the cFP-2020 through sensors in the engine and then transmitted wirelessly to the PC Ethernet port. The architecture allows to control and monitor in real time variations in temperature and engine speed. It is designed and configured a wireless communication system based on the use of two Ubiquiti Nano Station, operating under the 802.11 standard in the 2.4 GHz, with maximum rate of 54 Mb/s to form a wireless network between PC and the cFP-2020. The communication link with the central server is done via TCP / IP. The three-motor phase "squirrel cage" is attached to a conveyor belt (existing laboratory automation), which has been the automation and improvement of this machine as it will allow on, off, increase or decrease its speed, reverse direction of rotation, play alarm signals from remote.